الأوبئة وفلسفة الفن - زينب, لوت (roa, 2021)
يلامسُ الفنان الواقع من أجل محاكاة الوجود وتمثيله جماليا عبر اللغة أو التشكيل اللوني أو المسرح لذلك يعد الوباء من الأمراض التي تهدد حياة الانسان ومن خاصيتها الانتشار والعدوى التي تحدث في إطار تدريجي حتى تتسع ويصبح خطرها أكثر تهديدا للموجودات الكائنة، لذلك يكون التعبير عن الذات فلسفة بقاء ومقاومة للفنان، هي ملحمة يثيرها الفنانون درءا للنسيان وتخليدا للأزمات وأثارها على البشرية، تتكون الدراسة من محاور حول المفاهيم الأولية للأوبئة، الحكي وتأثيره في زمن انتشار الفيروسات والامراض، الرسم وعلاقته في تشكيل اللوحة الوبائية. إشكالية الدراسة: ماهي الفلسفة الفنية في خضم المعناة الوبائية؟  كيف توظف الآثار الأدبية صورة الوباء؟ هل اللون تشكيل للحس النفسي للأوبئة وتصميم للحياة بين التعايش وأمل التعافي؟ أين يقع الفنان في تجسيد المعاناة أم في تبئير الذات والآخر عبر الجمالية التي تفتح أفق التوقع؟ الكلمات المفتاحية: الفن- الفلسفة- الوباء- المحكي- الرسم- المسرح-الأثر. Summary: The artist touches reality in order to simulate existence and represent it aesthetically through language, chromatic composition, or theater. Therefore, the epidemic is a disease that threatens human life and its characteristic is the spread and infection that occurs in a gradual framework until it expands and its danger becomes more threatening to the existing assets, so self-expression is a philosophy of survival And resistance to the artist, it is an epic that artists raise in order to ward off oblivion and perpetuate crises and their effects on humanity, the study consists of axes on the initial concepts of epidemics, narration and its impact in the time of the spread of viruses and diseases, drawing and its relationship in the formation of epidemiological painting. The problem of the study: What is the artistic philosophy in the midst of the epidemiological meaning? How do literary monuments employ the epidemic picture? Is color shaping the psychological sense of epidemics, a design for life between coexistence and the hope of recovery? Where is the artist located in the embodiment of suffering or in focusing on the self and the other through the aesthetic that opens the horizon of expectation?